The Application of Telemedicine in Orthopedic Surgery in Singapore: A Pilot Study on a Secure, Mobile Telehealth Application and Messaging Platform - Daruwalla, Zubin Jimmy; Wong, Keng Lin; Thambiah, Joseph (JMIR Publications, 2014)
BackgroundThe application of telemedicine has been described for its use in medical training and education, management of stroke patients, urologic surgeries, pediatric laparoscopic surgeries, clinical outreach, and the field of orthopedics. However, the usefulness of a secure, mobile telehealth application, and messaging platform has not been well described. ObjectiveA pilot study was conducted to implement a health insurance portability and accountability act (HIPAA) compliant form of communication between doctors in an orthopedic clinical setting and determine their reactions to MyDoc, a secure, mobile telehealth application, and messaging platform. MethodsBy replacing current methods of communication through various mobile applications and text messaging services with MyDoc over a six week period, we gained feedback and determined user satisfaction with this innovative system from questionnaires handed to the program director, program coordinator, one trauma consultant, all orthopedic residents, and six non-orthopedic residents at the National University Hospital in Singapore. ResultsAlmost everyone who completed the questionnaire strongly agreed that MyDoc should replace current systems of peer to peer communication in the hospital. The majority also felt that the quality of images, videos, and sound were excellent. Almost everyone agreed that they could communicate easily with each other and would feel comfortable doing so routinely. The majority felt that virtual consults through MyDoc should be made available to inpatients as well as outpatients to potentially lessen clinic loads and provide a secure manner in which patients can communicate with their primary teams any time convenient to both. It was also agreed by most that the potential of telerounding had advantages, especially on weekends as a supplement to normal rounds. ConclusionsPotential uses of MyDoc in an orthopedic clinical setting include HIPAA-compliant peer to peer communication, clinical outreach in the setting of trauma, supervision in the operating room or watching procedures being performed remotely, providing both patient and parent reassurance in pediatric orthopedic patients, and finally in the setting of outpatient clinics. With our pilot study having excellent results in terms of acceptance and satisfaction, the integration of a secure, mobile telehealth application, and messaging platform, not only in the orthopedic department but also the hospital in general, has an exciting and limitless potential. More so in this era where downsizing hospital costs is beneficial, doing so may also be mandatory in order to comply with the soon to be introduced personal data protection act.